Evaluation and Comparison of AAA and AXB Dose Calculation Algorithms for Lung SBRT on TrueBeam STx with Eclipse 13.6 - Pham , Hong Lam; Phan , Tien Dung; Vu , Phuong Quy; Pham , Quang Trung (Nuclear Science and Technology, 2026)
This study aims to comprehensively evaluate and compare lung Stereotactic Body Radiation Therapy (SBRT) dose distribution using the Eclipse v13.6 treatment planning system and TrueBeam STx linac data, employing two dose calculation algorithms: Analytical Anisotropic Algorithm (AAA) and Acuros External Beam (AXB). Utilizing thirty-five 4DCT lung SBRT datasets, dose calculations were performed with both algorithms, maintaining consistent setup conditions except for the varied calculation algorithm. Evaluation criteria included tumor dose distribution Conformity Index (CI), Homogeneity Index (HI), Gradient Index (GI), D2cm, V105%, Dmax and organs-at-risk (OAR) doses, assessed via Dose Volume Histogram (DVH) analysis. Additionally, linac parameters such as Monitor Unit (MU) and Beam on Time (BoT) were analyzed. Both algorithms met dose criteria for tumors and OAR tolerance. Minor differences were observed in tumor distribution indices, with AXB’s Gradient Index showing proximity to ideal values. Although AXB exhibited slightly higher OAR doses, differences were statistically insignificant. AXB also demonstrated reduced average MUs and BoT. This comparative analysis underscores the efficacy of both AAA and AXB algorithms in ensuring dose conformity and OAR tolerance in lung SBRT planning, with AXB potentially offering improvements in efficiency and patient safety.